Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's tackle the question step by step.
### Determining the Number of Terms in the Given Series:
#### Series (a): [tex]\(5 + 8 + 11 + \ldots + 320\)[/tex]
1. Identify the first term ([tex]\(a_1\)[/tex]) and the common difference ([tex]\(d\)[/tex]):
[tex]\[ a_1 = 5, \quad d = 3 \][/tex]
2. Identify the last term ([tex]\(a_n\)[/tex]):
[tex]\[ a_n = 320 \][/tex]
3. Use the formula for the [tex]\(n\)[/tex]-th term of an arithmetic series:
[tex]\[ a_n = a_1 + (n - 1) \cdot d \][/tex]
Rearrange to solve for [tex]\(n\)[/tex]:
[tex]\[ n = \frac{a_n - a_1}{d} + 1 \][/tex]
4. Substitute the given values:
[tex]\[ n = \frac{320 - 5}{3} + 1 = \frac{315}{3} + 1 = 105 + 1 = 106 \][/tex]
So, the series has 106 terms.
#### Series (c): [tex]\(10 + 13 + 16 + \ldots + 49\)[/tex]
1. Identify the first term ([tex]\(a_1\)[/tex]) and the common difference ([tex]\(d\)[/tex]):
[tex]\[ a_1 = 10, \quad d = 3 \][/tex]
2. Identify the last term ([tex]\(a_n\)[/tex]):
[tex]\[ a_n = 49 \][/tex]
3. Use the formula for the [tex]\(n\)[/tex]-th term of an arithmetic series:
[tex]\[ a_n = a_1 + (n - 1) \cdot d \][/tex]
Rearrange to solve for [tex]\(n\)[/tex]:
[tex]\[ n = \frac{a_n - a_1}{d} + 1 \][/tex]
4. Substitute the given values:
[tex]\[ n = \frac{49 - 10}{3} + 1 = \frac{39}{3} + 1 = 13 + 1 = 14 \][/tex]
So, the series has 14 terms.
#### Series (b) and (d) cannot be solved as they do not provide sufficient information (e.g., the last term of the series is not given).
### Determine the Common Difference and First Term for the Specific Conditions:
#### (a) [tex]\(10^{\text{th}}\)[/tex] Term [tex]\(= 23\)[/tex] and [tex]\(32^{\text{nd}}\)[/tex] Term [tex]\(= 67\)[/tex]:
1. Use the general formula for the [tex]\(n\)[/tex]-th term of an arithmetic series:
[tex]\[ a_n = a_1 + (n - 1) \cdot d \][/tex]
2. Write two equations using the given terms:
[tex]\[ \begin{cases} a_1 + 9d = 23 \quad & \text{(for the 10th term)} \\ a_1 + 31d = 67 \quad & \text{(for the 32nd term)} \end{cases} \][/tex]
3. Subtract the first equation from the second:
[tex]\[ (a_1 + 31d) - (a_1 + 9d) = 67 - 23 \\ 22d = 44 \\ \][/tex]
4. Solve for [tex]\(d\)[/tex]:
[tex]\[ d = \frac{44}{22} = 2 \][/tex]
5. Substitute [tex]\(d\)[/tex] back into one of the original equations to find [tex]\(a_1\)[/tex]:
[tex]\[ a_1 + 9 \cdot d = 23 \\ a_1 + 9 \cdot 2 = 23 \\ a_1 + 18 = 23 \\ a_1 = 23 - 18 \\ a_1 = 5 \][/tex]
Thus, the first term [tex]\(a_1 = 5\)[/tex] and the common difference [tex]\(d = 2\)[/tex].
#### (b) [tex]\(11^{\text{th}}\)[/tex] Term [tex]\(= 5\)[/tex]
The provided information is incomplete and does not allow us to find the first term and the common difference. More information is required to solve this part.
### Summary:
- Series (a) has 106 terms.
- Series (c) has 14 terms.
- The first term and common difference for the series whose [tex]\(10^{\text{th}}\)[/tex] term is 23 and [tex]\(32^{\text{nd}}\)[/tex] term is 67 are 5 and 2, respectively.
- Insufficient information is provided to solve for series (b) and (d).
### Determining the Number of Terms in the Given Series:
#### Series (a): [tex]\(5 + 8 + 11 + \ldots + 320\)[/tex]
1. Identify the first term ([tex]\(a_1\)[/tex]) and the common difference ([tex]\(d\)[/tex]):
[tex]\[ a_1 = 5, \quad d = 3 \][/tex]
2. Identify the last term ([tex]\(a_n\)[/tex]):
[tex]\[ a_n = 320 \][/tex]
3. Use the formula for the [tex]\(n\)[/tex]-th term of an arithmetic series:
[tex]\[ a_n = a_1 + (n - 1) \cdot d \][/tex]
Rearrange to solve for [tex]\(n\)[/tex]:
[tex]\[ n = \frac{a_n - a_1}{d} + 1 \][/tex]
4. Substitute the given values:
[tex]\[ n = \frac{320 - 5}{3} + 1 = \frac{315}{3} + 1 = 105 + 1 = 106 \][/tex]
So, the series has 106 terms.
#### Series (c): [tex]\(10 + 13 + 16 + \ldots + 49\)[/tex]
1. Identify the first term ([tex]\(a_1\)[/tex]) and the common difference ([tex]\(d\)[/tex]):
[tex]\[ a_1 = 10, \quad d = 3 \][/tex]
2. Identify the last term ([tex]\(a_n\)[/tex]):
[tex]\[ a_n = 49 \][/tex]
3. Use the formula for the [tex]\(n\)[/tex]-th term of an arithmetic series:
[tex]\[ a_n = a_1 + (n - 1) \cdot d \][/tex]
Rearrange to solve for [tex]\(n\)[/tex]:
[tex]\[ n = \frac{a_n - a_1}{d} + 1 \][/tex]
4. Substitute the given values:
[tex]\[ n = \frac{49 - 10}{3} + 1 = \frac{39}{3} + 1 = 13 + 1 = 14 \][/tex]
So, the series has 14 terms.
#### Series (b) and (d) cannot be solved as they do not provide sufficient information (e.g., the last term of the series is not given).
### Determine the Common Difference and First Term for the Specific Conditions:
#### (a) [tex]\(10^{\text{th}}\)[/tex] Term [tex]\(= 23\)[/tex] and [tex]\(32^{\text{nd}}\)[/tex] Term [tex]\(= 67\)[/tex]:
1. Use the general formula for the [tex]\(n\)[/tex]-th term of an arithmetic series:
[tex]\[ a_n = a_1 + (n - 1) \cdot d \][/tex]
2. Write two equations using the given terms:
[tex]\[ \begin{cases} a_1 + 9d = 23 \quad & \text{(for the 10th term)} \\ a_1 + 31d = 67 \quad & \text{(for the 32nd term)} \end{cases} \][/tex]
3. Subtract the first equation from the second:
[tex]\[ (a_1 + 31d) - (a_1 + 9d) = 67 - 23 \\ 22d = 44 \\ \][/tex]
4. Solve for [tex]\(d\)[/tex]:
[tex]\[ d = \frac{44}{22} = 2 \][/tex]
5. Substitute [tex]\(d\)[/tex] back into one of the original equations to find [tex]\(a_1\)[/tex]:
[tex]\[ a_1 + 9 \cdot d = 23 \\ a_1 + 9 \cdot 2 = 23 \\ a_1 + 18 = 23 \\ a_1 = 23 - 18 \\ a_1 = 5 \][/tex]
Thus, the first term [tex]\(a_1 = 5\)[/tex] and the common difference [tex]\(d = 2\)[/tex].
#### (b) [tex]\(11^{\text{th}}\)[/tex] Term [tex]\(= 5\)[/tex]
The provided information is incomplete and does not allow us to find the first term and the common difference. More information is required to solve this part.
### Summary:
- Series (a) has 106 terms.
- Series (c) has 14 terms.
- The first term and common difference for the series whose [tex]\(10^{\text{th}}\)[/tex] term is 23 and [tex]\(32^{\text{nd}}\)[/tex] term is 67 are 5 and 2, respectively.
- Insufficient information is provided to solve for series (b) and (d).
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.